Lipid droplet formation in HeLa cervical cancer cells depends on cell density and the concentration of exogenous unsaturated fatty acids - Ema Guštin; Eva Jarc; Ana Kump; Toni Petan (Acta Chimica Slovenica, 2017)
Cytosolic lipid droplets (LDs) store excess fatty acids (FAs) in the form of neutral lipids and prevent starvation-induced cancer cell death. Here we studied the ability of mono- and polyunsaturated FAs to affect LD formation and survival in Hela cervical cancer cells. We found that the LD content in Hela cells increases with cell density, but it decreases in MDA-MB-231 breast cancer cells. Exogenously-added unsaturated FAs, including oleic (OA), linoleic (LA), arachidonic (AA), eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), displayed a similar ability to alter LD formation in Hela cells. There was a dual, concentration-dependent effect: low micromolar concentrations suppressed, while higher concentrations of FAs induced LD formation. In serum starved Hela cells, OA stimulated LD formation, but, contrary to expectations, it promoted cell death. Our results reveal a link between cell population density and LD formation in Hela cells and show that unsaturated FAs may both suppress and stimulate LD formation. This dynamic regulation of LD content must be accounted for when studying the effects of lipids and lipid metabolism-targeting drugs on LD metabolism in HeLa cells.